Inhibition of Mg Corrosion by Sulfur Blocking of the Hydrogen Evolution Reaction on Iron Impurities. Issue 12 (25th August 2020) - Mercier, Dimitri; Światowska, Jolanta; Protopopoff, Elie; Zanna, Sandrine; Seyeux, Antoine; Marcus, Philippe
Abstract : A combination of electrochemical measurements, H2 volume measurements and surface analysis using Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) and X-ray Photoelectron Spectroscopy (XPS) was used to investigate the role of the metallic Fe impurities (60 ppm) in high purity (99.9 wt%) magnesium and the effect of sulfur on the hydrogen evolution. The Mg corrosion was studied in NaCl solutions containing dissolved hydrogen sulfide. At OCP and under anodic polarization the hydrogen evolution reaction and the growth of dark corroded areas were significantly inhibited in the presence of H2 Saq . ToF-SIMS and XPS analyses showed the presence of sulfur adsorbed on Mg and on Fe segregated at grain boundaries. The observed inhibition of hydrogen evolution at OCP and above is assigned to a poisoning effect by adsorbed S of the H adsorption sites on segregated iron which, in the absence of sulfur, provides catalytic sites for excess HER. The equilibrium Pourbaix diagram for the Mg–Fe–S system including the adsorbed species predicts that S is adsorbed on Mg and Fe in the E-pH conditions of this work, which confirms the role assigned to adsorbed sulfur in the inhibition of excess hydrogen evolution at OCP and under anodic polarization in the presence of H2 Saq.